PENGAWASAN DPR DAN POLITIK KARTEL ERA REFORMASI: STUDI KASUS INTERPELASI DANANGKET TAHUN 1999?2011 - Wawan Ichwanuddin (Masyarakat Indonesia, 2012)
Using Katz and Mairs perspective on the political cartel, this paper describes thereality of legislative oversight in the reformation era. This perspective explains thatpolitical parties are increasingly dependent on the state resources. Consequently, therelationship between political parties in the legislature and the voters they represent isweakened. The quantity of oversight conducted by the parliamentduring the reformation era does not necessarily indicate the quality of the representation. The process andoutcome of the inquiries and interpellations proposed in the parliamentrepresent theinterests of the parties rather than that of the people. The competition in the parliamentis merelya political bargaining mechanism among political parties, particularly to getaccess to the public resources. With costlycampaigns, all parties arehighly dependenton the state finances. There are various corruption cases involving politicians fromdifferent parties, which are evidenced of the phenomenon of political cartel.Keywords: legislative oversight, DPR, Era Reformasi, eartelization